2016
DOI: 10.1007/978-3-319-54660-5_37
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Manipulator Performance Measurement Towards Manufacturing Assembly Tasks

Abstract: Mobile manipulator performance measurement research is relatively minimal as compared to that of robot arms. Measurement methods, such as optical tracking systems, are useful for measuring the performance of mobile manipulators, although at a much higher relative cost as compared to artifacts. The concept of using test artifacts demonstrates to potential manufacturers and users of mobile manipulator systems that relatively low cost performance measurement methods exist. This paper discusses the concept of reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…During development, an optical tracking measurement system [14, 15] was used as ground truth. The optical tracker could simultaneously measure the position of all system components.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During development, an optical tracking measurement system [14, 15] was used as ground truth. The optical tracker could simultaneously measure the position of all system components.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Recent research [14] demonstrated registration of the mobile manipulator to 1 mm diameter fiducials from any vehicle orientation with respect to the RMMA-1. The registration method incorporated a 0.5 mm step, square-spiral search pattern, and higher resolution A-UGV pose information (0.01 mm position and 0.01° orientation).…”
Section: Astm F4502 Docking and Navigationmentioning
confidence: 99%
“…NIST has been developing a mobile manipulator, performance measurement concept over the past two years [3,4,5]. This concept, which evolved from the experiments described in [6], consists of using 1) a NIST-developed, reconfigurable, mobile manipulator artifact (RMMA) (see Figure 1) with 2) interchangeable and varying sized fiducials to be detected by a sensor carried by the mobile manipulator.…”
Section: Mobile Manipulator Performance Measurement Conceptmentioning
confidence: 99%
“…The current location and orientation of the AGV were recorded. The arm was repositioned manually until the sensor detected alignment [3,5,6] with each of the index fiducials, and the manipulator position was recorded. This information, along with the position of the manipulator base relative to the vehicle's coordinate system, allowed the correct manipulator coordinates for the index fiducials to be calculated for an arbitrary AGV location.…”
Section: Mobile Manipulator Algorithmmentioning
confidence: 99%
“…A simple and low-cost method for calibrating and measuring the performance of this mobile manipulator is formulated by wielding a laser retroreflector to the robotic manipulator as an end-ofarm-tool. The retroreflector has a binary output which turns on when it detects a reflector (target) that is attached to a Reconfigurable Mobile Manipulator Artifact (RMMA) [2,3]. The horizontal two-dimensional (2D) position of the robot arm with respect to its base is recorded when a reflector is detected.…”
Section: Introductionmentioning
confidence: 99%